Penilaian Hasil Pelatihan Pemeliharaan Kesehatan Gigi dan Mulut di Era Pandemi COVID-19 pada Karyawan Yvonne’s Catering, Cipinang Muara - Monica Dewi; Himawan Halim; Joko Kusnoto; Yayuk Yuliarsi; Johni Halim; Maureen A. Wongso; Holie Fransiski (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Since early March 2020 until today, COVID-19 case in Indonesia is still a problem, requiring comprehensive efforts to manage and break the chain of transmission. Employees of Yvonne's Catering located in Cipinang Muara, possess oral health problems such as cavities, swollen gums, bad breath, and significant number of tooth loss. These problems affect employees' day-to-day performance – bad breath gets in the way of employees talking to customers, and toothaches affect employees while working in the kitchen. During the COVID-19 pandemic, people were afraid to have their teeth checked by dentists because dental treatment was considered a high risk of transmission of COVID-19 infection. Based on the problems above, Yvonne's Catering employees need training and education about the importance of maintaining oral health to prevent cavities which are closely related to overall health, and providing an understanding of emergency cases that need to be treated immediately to prevent the conditions from worsening that can be life-threatening. Information regarding the importance of implementing the 5M health protocol (wearing mask, washing hands, keeping distance, staying away from crowds, and reducing mobility) to protect oneself from exposure to the COVID-19 virus was also provided, including when visiting dentists. The main purpose of this community service is to increase the knowledge and skills of the community in maintaining maximum oral hygiene. Other goals in this community service include providing alternatives as an effort to maintain oral hygiene and health by making their own mouthwash using natural ingredients from their surroundings, such as Ocimum basilicum.